Problematika Praperadilan Dalam Rangka Pemenuhan Hak-Hak Tersangka - Arios Valentino Taghupia; John Dirk Pasalbessy; Deassy Jacomina Anthoneta Hehanussa (Postgraduate Program in Law, Universitas Pattimura, 2022)
Introduction: The pretrial examination only examines the validity of legal procedures in handling cases. The question which one should be the subject of a pretrial case examination, whether the examination of the procedure, or examination of the subject matter.Purposes of the Research: This study aims to analyze and discuss of the essentially examination of pretrial cases an effort to fulfil one’s rights of the suspect according of the criminal procedure code, and Objectivity of pretrial case examination and its presence in the criminal procedure code in the future.Methods of the Research: The type of research is normative legal research. The approach used in this research are the statutory approach, conceptual approach, and case approach. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials are through literature study, and analysis of legal materials is qualitative.Results of the Research: The pretrial examination mechanism which is essentially an effort to fulfil one's rights in its implementation is not so broad in the sense that the examination of cases that are substantial (material aspects) in the context of actual prove of a procedure law enforcement. To obtain a material truth, the judge in examining existing pretrial case, has not been able to explore the truth in assessing any evidence submitted by the applicant and the respondent in a pretrial case, which also means that in some pretrial case examinations, judge are still limited to pretrial examination, namely regarding the procedure as stipulated in article 77 of the Criminal Procedure Code.